IDENTIFICATIONS OF DRUG RELATED PROBLEMS ON HOSPITALIZED PATIENTS WITH ASTHMA IN PKU MUHAMMADIYAH YOGYAKARTA HOSPITAL IN 2009 - Fitria Nur Hidayah; Septimawanto Dwi Prasetyo (Faculty of Pharmacy, Universitas Gadjah Mada)
The change of pharmacy services paradigm from drug-oriented to patient-oriented (pharmaceutical care) requires an increase in the role of pharmacist in patient therapy. In order to support it, identification of Drug Related Problems (DRPs) is necessary. DRPs are problems that arise in drug therapy that could affect the outcome of patient therapy. DRPs are following the increase of types and amount of drugs consumed by patients, especially in the treatment of chronic diseases. Asthma is a chronic disease with increasing prevalence each year. The purpose of this study is to identify the incidence of DRPs in hospitalized patient with asthma. This study is a non-experimental descriptive research. Data collection was done retrospectively on the medical records card of hospitalized patients with asthma at PKU Muhammadiyah Yogyakarta Hospital in 2009. The data obtained were then analyzed with descriptive analysis. DRPs being analyzed include need for additional drug therapy, unnecessary and duplication drug therapy, wrong drug, dosage too low, drug interaction, and dosage too high. The results showed that the precentage of patients with DRPs was 55% (55 patients) and there were a total of 75 DRPs occured. The percentage incidence of each category were need for additional drug therapy is 16,0% , unnecessary and duplication drug therapy is 21,3%, wrong drug is 10,7%, dosage too low is 18,7%, drug interaction is 12,0%, and dosage too high is 21,3%. Key words : hospitalized patients with asthma, Drug Related Problems (DRPs), PKU Muhammadiyah Yogyakarta Hospital